PENGARUH PENGGUNAAN METODE OUTDOOR LEARNING TERHADAP HASIL BELAJAR IPA - Hidayanti, Reza Aura; Herpratiwi, Herpratiwi; Sulistianah, Sulistianah; Mashari, Ali (AHSANTA JURNAL PENDIDIKAN, 2024)
The problem in this study is that the learning outcomes of students are still low. This study aims to determine that the use of outdoor learning methods can be used to improve the Science Learning Outcomes of Grade V Students of SD Negeri 1 Jatibaru South Lampung. This research is quantitative research with the type of pre-experiment using the form of one group pretest posttest. The population in this study amounted to 58 students and the sample used amounted to 29 students using random sampling technique. Data analysis in this study used normality test and homogeneity test then hypothesis testing was carried out. Based on the results of research that has been conducted by researchers, it can be seen that hypothesis testing obtained the results of Tcount > Ttable, namely Tcount of 11,184 with Ttable 1,701 with a significant level (2-tailed) 0.000 <0.05. This means that ???????? is accepted and ????0 is rejected. Thus the use of the Outdoor learning method affects the Science Learning Outcomes of Grade V Students of SD Negeri 1 Jatibaru South Lampung